Abstractions Based on Circles : Papers on prehistoric rock art presented to Stan Beckensall on his 90th birthday - Frodsham, Paul (Archaeopress Publishing, 2022)
Stan Beckensall is renowned for his work, done on an entirely amateur basis, discovering, recording and interpreting Atlantic rock art in his home county of Northumberland and beyond. Presented on his 90th birthday, this diverse and stimulating collection of papers celebrates his crucial contribution to rock art studies, and looks to the future.